Climate Information Needs and Channel Preferences among Smallholder Farmers in Ethiopia - Tesfaye, Kindie; Mekuriaw, Abate; Ejeta, Alemu T. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate information provisions are mostly supply-driven and not tailored to the needs of farmers and communities. Moreover, studies on climate information services in Ethiopia are scanty and pay less attention to climate-risk-related information needs and delivery channel preferences of smallholder farmers. Therefore, a study was conducted to assess major climate risks, climate information needs and preferred climate information delivery channels among farming communities in the major crop-livestock systems. Respondents identified the major climate and climate-related risks in the Belg and Meher seasons. Household heads, spouses and expert respondents agreed on most of the climate risks, although there were differences in the rating of some of the climate risks. Almost all respondents acknowledge that they received climate information mostly once a season and used it to plan for land preparation operations only. According to the respondents, Development Agents (DAs), kebele meetings, radio, and religious gatherings are the most common sources of climate information. More than 95% of the household head and spouse respondents expressed their strong desire to receive climate information services, preferably through DAs, radio and kebele meetings.